Analisis Tingkat Kepuasan Masyarakat Terhadap Layanan Pemberdayaan Potensi Sumber Kesejahteraan Sosial - Rizki, Muhammad Bagus; Pakereng, Magdalena A. Ineke (STIKOM Tunas Bangsa Pematangsiantar, 2022)
Along with the increasing number of people who need social assistance, companies engaged in their fields are required to improve the quality of their services, one of which is the Semarang Regency Social Service. Determination of the level of service satisfaction of the Semarang Regency Social Service is done by distributing questionnaires to the public who visit or use the Semarang Regency Social Service's service facilities. The results of the questionnaire are then described in the Cartesian Importance-Performance Analysis (IPA) diagram and the Customer Satisfaction Index (CSI) value which shows overall user satisfaction. The Cartesian IPA diagram shows that the attributes of aspects and requirements that must be met, the time given, the amount of the tariff, to the quality and service facilities provided by the community at the Semarang Regency Social Service. The overall level of service satisfaction is indicated by a CSI value of 83.59, which means that users or the public are very satisfied with the services provided by the Semarang Regency Social Service